Faktor Risiko Feline Panleukopenia pada Kucing di Daerah Istimewa Yogyakarta - Riyandini Putri; Bambang Sumiarto; Guntari Titik Mulyani (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2020)
AbstractFeline panleukopenia virus (FPV) infection in cats caused a disease called feline panleukopenia with high morbidity and mortality worldwide. There is no causative therapy for this disease yet, therefore knowing risk factors is important measure to prevent the disease. This study was designed to investigate the risk factors of feline panleukopenia in Special Region of Yogyakarta therefore disease prevention can be done as early as possible. A retrospective case-control study that used 35 cats in the case group and 70 cats in the control group. Case group consisted all feline panleukopenia patients that were tested positive with Anigen FPV Ag Test Kit (Bionote, South Korea) from two local clinics. Control group consisted cats that were own by the neighbour of cats from the case group with age and sex as matching variables. Owner characteristics including formal education, occupation, duration of having cat(s), monthly maintenance cost, and interaction time per day also feline characteristics including breed, neuter status, origin, husbandry, and vaccination status were assessed. Association analysis was done using EpiInfo (chi-square and odds ratio) and manually calculated (estimated attributable fraction and estimated population attributable fraction). Associated risk factors of feline panleukopenia were duration of having cat(s) less than a year, domestic cat breed, cat origins such as pet store or market and stray cat, the presence of new cat(s), outdoor cat lifestyle, waste disposal outdoor, and not vaccinated cat. Vaccination status and the presence of new cat(s) had the highest strength compared to other risk factors. It can be concluded that vaccination and quarantine of new animals are important measures to prevent feline panleukopenia.Keywords: case-control study, cats, feline panleukopenia